Head injuries and emergencies in sports - Rao, A. L.; Song, L.; Griffin, G. (Clinics in Sports Medicine, 2023)
Head injuries represent an important injury designation, for which sports medicine providers should be prepared to recognize, manage, and appropriately triage.